A mosaic of understanding: fusing perspectives to legitimize non-technical ways of knowing climate change - Drake, Erin Marie, author; Thompson, Jessica, advisor; Champ, Joseph, committee member; Melena, Sara, committee member (Colorado State University. Libraries, 2012)
The impacts and implications of climate change are as diverse as the global community faced with addressing this social-ecological issue. Expert-driven communication strategies that emphasize an abundance of scientific information laden with technical language and positivist values have insufficiently appealed to non-technical audiences. This shortcoming has widened the gap between technical and non-technical publics and fails to acknowledge the legitimacy of different forms of expertise that include social dimensions of climate change. Different ways of knowing have also been ignored, largely reducing climate change communication to static, one-way presentations of climate science information. Iterative, interactive, and tangible learning processes are underrepresented in climate change communication efforts but can better resonate and engage many non-technical audiences. The power of place-based connections and communication allows for non-technical publics to relate to global climate change through the familiarity and appreciation of local landscapes. National parks and wildlife refuges, places of public value and trust, can seed connections between non-technical visiting publics and climate change. Non-technical audiences can better relate to and understand climate change through the renegotiation of language, relevance, and resonant messages framed in a valued landscape - essentially through the lens of place. These connections, in tandem with hands-on engagement practices, can foster a network of engaged climate change citizens with the capacity to inspire others outside of parks and refuges.
Keywords: expertise; climate change; communication; non-technical; place-based; ways of knowing